Causal agent of red stripe disease of rice - Elazegui, F.A.; Castilla, N.P.; Dalisay, T.U.; Mew, T.W. (Scientific Societies, 2004)
A variety of methods that included natural and synthetic media for isolating bacteria and fungi were used to isolate the causal agent of the red stripe disease of rice. A fungus was isolated consistently from leaves with red stripe symptoms using the blotter method. In this method, surface-sterilized leaves were placed on sterile petri plates, lined with moistened filter paper, and the plates were incubated for 14 days at 28 to 30°C. The fungal isolate was reisolated from the lesions of inoculated plants and reinoculated on test plants that became symptomatic, thus fulfilling Koch's postulates. Based on the morphological characteristics of the fungus, the causal agent of red stripe was identified as a species of Gonatophragmium. Colonies of the latter are slow-growing, reaching an average of 29.0 ± 0.9 mm in diameter after incubation on potato dextrose agar (PDA) for 18 days at 28 to 30°C in the dark. It can be overgrown easily by saprophytes when infected leaves are incubated using the blotter method without sterilization. Yellow-orange pigmentation was observed on PDA with mycelial growth and on filter paper with infected leaves, a unique characteristic which facilitates the isolation of the fungus. Studies are in progress using traditional and molecular techniques to identify the pathogen to the species level.